Anticholinesterase activity of Areca Catechu: In Vitro and in silico green synthesis approach in search for therapeutic agents against Alzheimer’s disease - Pradeep, Sushma; Prabhuswaminath, Samudyata C.; Reddy, Pruthvish; Srinivasa, Sudhanva M.; Shati, Ali A.; Alfaifi, Mohammad Y.; Eldin I. Elbehairi, Serag; Achar, Raghu Ram; Silina, Ekaterina; Stupin, Victor; Manturova, Natalia; Glossman-Mitnik, Daniel; et al. (Frontiers in Pharmacology, 2022)
For many years, the primary focus has been on finding effective treatments for Alzheimer's disease (AD), which has led to the identification of promising therapeutic targets. The necessity for AD stage-dependent optimal settings necessitated a herbal therapy strategy. The plant species Areca Catechu (AC) was selected based on the traditional uses against CNS-related diseases. AC leaf extract were prepared using a Soxhlet extraction method and hydroxyapatite nanoparticles (HAp NPs) were synthesized from the same (AC-HAp NPs). Powder X-ray diffractometer (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM) and selected area electron diffraction (SAED) were used to confirm the structure and morphology of the as-prepared AC-HAp NPs. The crystalline character of the AC-HAp NPs was visible in the XRD pattern. The synthesized material was found to be nanoflake, with an average diameter of 15 to 20 nm, according to SEM analysis. The TEM and SAED pictures also revealed the form and size of AC-HAp NPs. In vitro anti-acetylcholinesterase and butyrylcholinesterase (AChE and BChE) activities of hydroxyapatite nanoparticles produced from an AC leaf extract was tested in this study. When compared to control, AC-HAp NPs had higher anti-AChE and BChE activity. The anti-acetylcholinesterase action of phytoconstituents generated from AC leaf extract was mediated by 4AQD and 4EY7, according to a mechanistic study conducted utilizing in silico research. The MN12SX/Def2TZVP/H2O model chemistry has been used to predict the global and local descriptors, which are the cornerstones of Conceptual Density Functional Theory (CDFT), to aid in understanding the chemical reactivity features of the five ligands taken into consideration in this study. The CDFT experiments are supplemented by the calculation of several useful calculated pharmacokinetics indices, their expected biological targets, and the ADMET parameters connected to the bioavailability of the five ligands in order to further the goal of studying their bioactivity.